PERPADUAN BUDAYA HINDU DAN BUDDHA DI PURA GOA GIRI PUTRI NUSA PENIDA - Ni Made Suwendri (Universitas Warmadewa, 2026)
This study aims to examine the mechanisms through which Hindu and Buddhist cultures converged at the Goa Giri Putri Temple, identify the manifestations of this fusion, and uncover the values?inherent within it. This study applies the theory of cultural acculturation as an analytical tool to understand the dynamics of the meeting of these two religious traditions, while the theory of multiculturalism is used to explore the dimensions of meaning emerging from this fusion. The approach used was qualitative, with data collected through in-depth interviews and field observations, supported by a review of relevant literature. The analysis was descriptive and analytical. The results revealed two main factors driving this acculturation: the openness of the local community to the influx of Chinese traditions into the Hindu cultural environment, and the strong beliefs and convictions held by the local community. This acculturation can be observed through the presence of Buddhist statues placed side by side with shrines for Hindu deities within the Goa Giri Putri area. The ritual instruments used also do not differentiate between the two faith traditions. At the level of meaning, the Hindu-Buddhist acculturation the Temple conveys a message of multiculturalism and socio-religious values to the people of Karangsari, Suana Village, Nusa Penida, while fostering an attitude of sympathy, appreciation, and tolerance amidst religious and cultural diversity.